Behavioural patterns and morphological advantages favour successful use of Crematogaster schmidti trails by Camponotus lateralis WORKERS (HYMENOPTERA: FORMICIDAE) - Stukalyuk, Stanislav; Gladun, Dmytro; Akhmedov, Ascar (Penerbit Universiti Kebangsaan Malaysia, 2023)
The paper examines the relationship between two ant species: Camponotus lateralis and Crematogaster schmidti in the neighboring habitat in the biocenoses of the Southern Coast of the Crimea (Ukraine). The ecological characteristics of the species are given, the structure of forage areas is described, as well as the daily activity of ants in shared habitats. It was shown that Camponotus lateralis accesses the food resources of Crematogaster schmidti using their trails. As a result of a frame-by-frame analysis of the video recordings, a number of behavioural responses have been identified for each species that it displays during interspecific contacts on the trails. It was shown that Camponotus lateralis successfully avoids contact by changing its trajectory at a distance of about 1 cm from Crematogaster schmidti workers. The aggressive reaction of Crematogaster schmidti was only recorded in few cases after antenna contacts. In most cases, Camponotus lateralis reacted more quickly than Crematogaster schmidti after antennal contact and changed its trajectory. The structural characteristics of the antennae and eyes of workers of both species were compared. Camponotus lateralis workers were shown to have longer antennae on average. The eyes of Camponotus lateralis have, on average, more facets than those of Crematogaster schmidti and, on average, more facets per unit of eye area. The significance of these morphological advantages of Camponotus lateralis for the successful use of Crematogaster schmidti trails is discussed